Perivascular fluid cuffs decrease lung compliance by increasing tissue resistance - Lowe, Kevin; Alvarez, Diego F; King, Judy A; Stevens, Troy (Critical care medicine, 2010)
Lung inflammation causes perivascular fluid cuffs to form around extra-alveolar blood vessels; however, the physiologic consequences of such cuffs remain poorly understood. Herein, we tested the hypothesis that perivascular fluid cuffs, without concomitant alveolar edema, are sufficient to decrease lung compliance. Prospective, randomized, controlled study. Research laboratory. One hundred twenty male CD40 rats. To test this hypothesis, the plant alkaloid thapsigargin was used to activate store-operated calcium entry and increase cytosolic calcium in endothelium. Thapsigargin was infused into a central venous catheter of intact, sedated, and mechanically ventilated rats. Static and dynamic lung mechanics and hemodynamics were measured continuously. Thapsigargin produced perivascular fluid cuffs along extra-alveolar vessels but did not cause alveolar flooding or blood gas abnormalities. Lung compliance dose-dependently decreased after thapsigargin infusion, attributable to an increase in tissue resistance that was attributed to increased tissue damping and tissue elastance. Airway resistance was not changed. Neither central venous pressure nor left ventricular end diastolic pressure was altered by thapsigargin. Heart rate did not change, although thapsigargin decreased left ventricular systolic function sufficient to reduce cardiac output by 50%. Infusion of the type 4 phosphodiesterase inhibitor, rolipram, prevented thapsigargin from inducing perivascular cuffs and decreasing lung compliance. Rolipram also normalized pressure over time and corrected the deficit in cardiac output. Our findings resolve for the first time that perivascular cuff formation negatively impacts mechanical coupling between the bronchovascular bundle and the lung parenchyma, decreasing lung compliance without impacting central venous pressure.